Pengaruh Kepemilikan Saham, Keputusan Pendanaan, CSR dan Kinerja Keuangan Terhadap Nilai Perusahaan Jasa Konstruksi - Harsana Harsana; Wulansari Yusniar; Asrid Juniar (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2020)
This study aims to examine and analyze the effect of Managerial Ownership (X1), Institutional Ownership (X2), Financing Decision (X3), CSR (X4) and Financial Performance (X5) as independent variables either partially or simultaneously on Firm Value (Y) as the dependent variable in the Construction Services companies Listed on the Stock Exchange in 2014 - 2018. The method of this research used secondary data from the annual report 2014 to 2018 period in the study sample as many as 10 companies. Assessment of the effect of independent variables on the dependent variable used a multiple linear regression analysis with SPSS Ver. 25. The results of this study concluded that there is a significant negative effect of managerial ownership and institutional ownership on firm value. The financing decision is a significant positive effect on firm value. Meanwhile, both CSR and financial performance has no significant effect on firm value. Simultaneously, the independent variables can sufficiently explain the variation value of the company with 58.8% coefficient of determination.